Bringing to life Nomad Wisdom around leadership, strategy, and building strong communities - Valerie Jackman (University of Aberdeen, School of Education, 2021)
Colleges are rapidly changing in scale and scope and the current technological revolutions are contributing to the urgent need for a Learning Revolution. The COVID pandemic has pushed changes that have been beyond our reach for decades. However, to bring about the changes we really want to see, we need altruistic leadership and leadership that is agile, collaborative, and inclusive, as highlighted in the Cumberford-Little Report (2020). In June 2019, CDN introduced the Preparing for Executive Leadership (PEL) programme. It is not a qualification, rather an experiential programme that seeks to support leaders to draw on their own knowledge, experience, curiosity, and passion. Collaboration and a systems leadership approach sit at the heart, and the different components, which include less-traditional approaches such as Lego Serious Play, Equine-assisted Leadership, Solutions Focus and Service Design are facilitated by a diverse spectrum of specialists. The second cohort of PEL was due to start in June 2020 but COVID restrictions meant face to face gatherings were not possible. While this could have been seen as an impediment, we saw it as an opportunity to explore how we could enhance the programme and bring additional opportunities to support the unprecedented leadership challenges our 21st century educational leaders are facing.